Transforming Tourist Behavior in the Post-Pandemic Era : Big Data Insights from Jakarta’s Kotatua Heritage site - Fauziah Eddyono; Firnandi Gufron; Prasetiya, Budi (Unit Bahasa, Politeknik Pariwisata NHI Bandung, 2025)
The COVID-19 pandemic has profoundly reshaped tourist behavior, particularly within urban heritage destinations. This study explores the behavioural transformation of visitors to the Kotatua Jakarta heritage district before and after the pandemic, employing a descriptive quantitative approach grounded in big data analytics. A dataset of 692 user-generated reviews was extracted from multiple digital platforms—Tripadvisor, Google Review, Google Insight, and Traveloka—covering the period from 2016 to 2023. Structured data were analysed using SPSS, while unstructured textual data were processed through natural language processing techniques via RapidMiner and Python libraries. Findings indicate marked shifts in tourist segmentation, travel motivations, attraction preferences, visitation patterns, and spending behaviour. Post-pandemic tourists were predominantly local residents from Greater Jakarta, with Gen Z and Millennials comprising the majority. A transition was observed from educational motivations to light recreational and visual experiences such as photography and sightseeing. Average visit durations decreased, yet revisit intentions increased, while overall expenditure per visitor declined significantly. These trends reflect a growing demand for proximity-based, flexible, and value-conscious travel. The study underscores the imperative for destination management organisations (DMOs) to adopt data-driven strategies that prioritise digital engagement, open-air spatial design, and locally responsive tourism experiences. It further advocates for the sustained integration of big data analytics to support adaptive, inclusive, and sustainable governance of heritage tourism in the evolving post-pandemic context.